2015
DOI: 10.1186/s13023-015-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

High quality, patient centred and coordinated care for Alstrom syndrome: a model of care for an ultra-rare disease

Abstract: BackgroundPatients with rare and ultra-rare diseases make heavy demands on the resources of both health and social services, but these resources are often used inefficiently due to delays in diagnosis, poor and fragmented care. We analysed the national service for an ultra-rare disease, Alstrom syndrome, and compared the outcome and cost of the service to the standard care.MethodsBetween the 9th and 26th of March 2014 we undertook a cross-sectional study of the UK Alstrom syndrome patients and their carers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 13 publications
7
48
0
2
Order By: Relevance
“…Annual review clinics in a multidisciplinary team have been suggested for tertiary referral centres like ours with exams individually tailored to the complex needs of patients with ALMS and other ultra‐rare diseases for the convenience of the patients but also to serve as nuclei in driving large‐scale research in ultra‐rare diseases such as ALMS (Van Groenendael et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Annual review clinics in a multidisciplinary team have been suggested for tertiary referral centres like ours with exams individually tailored to the complex needs of patients with ALMS and other ultra‐rare diseases for the convenience of the patients but also to serve as nuclei in driving large‐scale research in ultra‐rare diseases such as ALMS (Van Groenendael et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Van Groenendael et al. ). Initially, the fundus appearance may be normal or near normal, eventually progressing to retinal dystrophy exhibiting attenuated vessels, pale optic discs and partial atrophy of the retinal pigment epithelium (RPE) without intraretinal pigment migration (Marshall et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied 23 patients attending a national specialized clinic for Alström syndrome (Van Groenendael et al. ). The spectrum of clinical severity was approximately in keeping with prior reports of the natural history of the syndrome (Michaud et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that a well-organised, patient-centred, multidisciplinary approach is more patient friendly and generates better outcomes than the current care model [19].…”
mentioning
confidence: 99%